FII and DII Inflows and Outflows: Their Influence on BSE Market Performance (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2024)
Purpose: The purpose of this paper is to analyze the impact of Foreign Institutional Investors (FII) and Domestic Institutional Investors (DII) on the performance of the Bombay Stock Exchange (BSE). By examining the patterns of inflows and outflows from these investors, the study aims to understand their influence on market trends, volatility, and overall performance. This analysis will provide insights for investors, policymakers, and financial analysts, helping them make informed decisions and develop strategies that consider the behaviours and effects of these significant market participants.Design/Methodology/Approach: This study employs a quantitative research methodology to analyze the impact of Foreign Institutional Investors (FII) and Domestic Institutional Investors (DII) on the Bombay Stock Exchange (BSE) market performance. The research utilizes secondary data collected from reliable financial databases and sources such as the BSE, SEBI, and financial reports. The study period spans the last 5 quarters, ensuring a comprehensive analysis of market trends and investor behaviour. The data includes daily, monthly, and yearly inflows and outflows of FII and DII, as well as corresponding BSE indices and stock prices.To assess the influence of FII and DII activities on market performance, statistical techniques such as correlation analysis, regression analysis, and time-series analysis are employed. These methods help identify patterns, relationships, and the extent of the impact of institutional investors on market trends and volatility.The analysis also includes a comparative examination of the behaviours and effects of FII and DII during different market conditions, such as periods of economic stability, market booms, and downturns. The results are further validated through robustness checks and sensitivity analyses to ensure the reliability and accuracy of the findings.Findings/Result: The analysis reveals that both Foreign Institutional Investors (FII) and Domestic Institutional Investors (DII) significantly influence the performance of the Bombay Stock Exchange (BSE). The study finds a strong correlation between FII inflows and positive market movements, indicating that foreign investments often drive market rallies. Conversely, substantial FII outflows tend to coincide with market declines, underscoring their role in market volatility. Domestic Institutional Investors, while also impactful, show a more stabilizing effect on the market. Their investment patterns are found to be less volatile compared to FIIs, often acting as a buffer during periods of heavy foreign outflows.Originality/Value: The paper's originality lies in its dual approach of evaluating both FII and DII activities concurrently, shedding light on their distinct and combined effects on market performance. By doing so, it offers valuable insights for investors, policymakers, and financial analysts, aiding in the development of more informed investment strategies and policy decisions. This research enhances the understanding of the dynamic roles that institutional investors play in shaping market behaviour, particularly in an emerging market context like India. Paper Type: Empirical Study
Keywords: Foreign Institutional Investors (FII); Domestic Institutional Investors (DII); Bombay Stock Exchange (BSE); Finance Sector; Power Sector; Correlation Analysis; Regression Analysis